INTERCONNECTEDNESS OF FOUR LANGUAGE SKILLS: WHY LITERATURE SHOULD BE A PART OF THE EFL CLASSROOM? - Abdullayeva Nigora Shavkatovna; Zuhriddinova Maftuna Zarifjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Integrating four language skills in English lessons provides benefits for both teachers and students. This article provides a comprehensive overview of key aspects of interconnectedness of four language skills, examining each of them in detail, significance of integration, and the role of literature in language learning process. The paper examines the benefits of including literary texts in the learning of English as a foreign language.